Piperacillin: In Vitro Evaluation - Bodey, Gerald P. (1978)
The in vitro activity of a new semisynthetic penicillin, piperacillin, was determined against 577 clinical isolates of gram-positive cocci and gram-negative bacilli. A concentration of 12.5 μg/ml inhibited 92% of isolates of Pseudomonas aeruginosa, 82% of Serratia marcescens, 73% of Escherichia coli, 61% of Klebsiella spp., and 42% of Enterobacter spp. Most Proteus spp. were extremely susceptible; over 85% were inhibited by 0.10 μg/ml. Piperacillin failed to inhibit the growth of gram-negative bacilli when large inocula were used. The type of media and pH had variable effects on the activity of piperacillin, depending upon the organism. Piperacillin was generally less active than PC-904 against gram-negative bacilli, but was consistently more active than carbenicillin and ticarcillin.